2013
DOI: 10.1539/joh.12-0252-oa
|View full text |Cite
|
Sign up to set email alerts
|

Work‐to‐family Conflict and Family‐to‐work Conflict among Japanese Dual‐earner Couples with Preschool Children: A Spillover‐Crossover Perspective

Abstract: Work-to-family Conflict and Family-towork Conflict among Japanese Dual-earner Couples with Preschool Children: A Spillover-Crossover Perspective: Akihito SHIMAZU, et al. Department of Mental Health, The University of Tokyo Graduate School of Medicine, Japan-Objectives: This study among Japanese dual-earner couples examined the independent and combined associations of work-tofamily conflict (WFC) and family-to-work conflict (FWC) with psychological health of employees and their partners and the relationship qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Husbands' traditional gender‐role attitudes may increase their wives' WFC for several reasons: for example, because a husband with strong traditional gender‐role attitudes invests less in the family domain (for an overview, see Davis & Greenstein, ), thereby increasing the wife's family burden, or because incongruence between husband's traditional gender‐role attitudes and the wife's employment causes conflicts between spouses (McHale & Crouter, ). Indeed, ample empirical evidence has shown that crossover between spouses can occur through negative marital interactions (e.g., Shimazu, Kubota, Bakker, Demerouti, Shimada, & Kawakami, ). Taken together, husbands' traditional gender‐role attitudes may increase the probability that the mother will perceive her work role as interfering with her family role, and will thereby lead to an increased experience of WFC.…”
Section: The Impact Of Spouses' Gender‐role Attitudes On Working Mothmentioning
confidence: 99%
“…Husbands' traditional gender‐role attitudes may increase their wives' WFC for several reasons: for example, because a husband with strong traditional gender‐role attitudes invests less in the family domain (for an overview, see Davis & Greenstein, ), thereby increasing the wife's family burden, or because incongruence between husband's traditional gender‐role attitudes and the wife's employment causes conflicts between spouses (McHale & Crouter, ). Indeed, ample empirical evidence has shown that crossover between spouses can occur through negative marital interactions (e.g., Shimazu, Kubota, Bakker, Demerouti, Shimada, & Kawakami, ). Taken together, husbands' traditional gender‐role attitudes may increase the probability that the mother will perceive her work role as interfering with her family role, and will thereby lead to an increased experience of WFC.…”
Section: The Impact Of Spouses' Gender‐role Attitudes On Working Mothmentioning
confidence: 99%
“…These results are indicative of gender differences when it comes to crossover of interrole conflict and are in line with some of the previous empirical findings. For example, Shimazu et al [29] in their study on a Japanese sample found that women's distress was caused by men's FWC but men's distress was unaffected by women's FWC. However, there is also a body of research which shows no gender differences in the crossover of interrole conflict [32].…”
Section: Discussionmentioning
confidence: 99%
“…H3a, H3b -hypotheses 3a and 3b: the impact of women's (men's) T1 job and family demands on men's (women's) change in work-and family-related stress is mediated by women's (men's) T1 interrole conflict (partner effects). outcomes such as distress [28,29], health [30], and relationship tension [31] are predicted not only by individual's own interrole conflict but also that of their partners'. However, a few aspects of the current body of research require addressing.…”
Section: Work and Family: Comparing The Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to applying the choice experiment method to the study of work-life balance and using the estimates to cast light on the issue of labor market reform in Japan, our contribution is to bring in a behavioral angle to the debate. It is often reported that guilt about work-life dilemmas tends to differ according to gender (Martínez, et al 2011), especially when issues of child-care are involved (Shimazu, et al 2013). As part of the experiment we investigate the extent to which guilt drives differences in the mean willingness of men and women to accept trade-offs in job features that affect work-life balance.…”
mentioning
confidence: 99%